Cenografia: um outro modo de experimentar e de praticar - Cristiano Cezarino Rodrigues (2013)
The aim of this research is to propose a theoretical framework that assists in the analysis of the contemporary scenography and, consequently, in their design processes. From the analysis of the issues raised by the development of practical works, some operators are listed in order to understand how the performing space is characterized nowadays. It is taken as hypothesis that the scenography operates to settle a territory that promotes possible alternative relations between action and reception. From this, one might question whether the scenography can promote a more engaging reception, and whether it is able to change the relationship between stage and audience. Perceives it is perceived that the contemporary performing arts and have developed several procedures that extend the performative and theatrical event that, in this turn, affects the notion of theatricality. Thus, we intend to understand how contemporary stage design is conceived as a relational practice space. One realizes that an intensive investigation on the different ways that define the relationship between action and receptiondirectly influences the creation of theatrical spatiality. This change of paradigm affects the very idea of scenography: it becomes a spatial practice that is practiced today, in order to catalyze flows and encode the bodies and movements of those who engage in scenic event.